2007
DOI: 10.1002/prot.21401
|View full text |Cite
|
Sign up to set email alerts
|

Structure networks of E. coli glutaminyl‐tRNA synthetase: Effects of ligand binding

Abstract: It is well known that proteins undergo backbone as well as side chain conformational changes upon ligand binding, which is not necessarily confined to the active site. Both the local and the global conformational changes brought out by ligand-binding have been extensively studied earlier. However, the global changes have been reported mainly at the protein backbone level. Here we present a method that explicitly takes into account the side chain interactions, yet providing a global view of the ligand-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…We do not treat side-chain conformational changes, which could be substantial even in the absence of a backbone conformational change, leading to residue rewiring. 25,26 Allosteric Effects Are Cooperative Cooperativity is nonindependence. Proteins are widely believed to fold cooperatively.…”
Section: Theory and The Allosteric Modelsmentioning
confidence: 99%
“…We do not treat side-chain conformational changes, which could be substantial even in the absence of a backbone conformational change, leading to residue rewiring. 25,26 Allosteric Effects Are Cooperative Cooperativity is nonindependence. Proteins are widely believed to fold cooperatively.…”
Section: Theory and The Allosteric Modelsmentioning
confidence: 99%
“…Hubs, the highly connected amino acids, are also identified from these networks. Furthermore, the hubs identified with this network CIs approach could be ideal targets for mutational studies to ascertain the ligandinduced SAR [194]. The indices reviewed above are useful only to seek protein sequence-function relationships.…”
Section: Tpgis or Cis For Free And Ligand-bound Proteinstructure Netwmentioning
confidence: 99%
“…In recent years, proteins were investigated as networks, by taking the amino-acids as nodes. Termed as residue networks (RN), edges between neighboring nodes are represented by their bonded and non-bonded interactions [16] , [17] , [18] , [19] . Several studies have shown that residue networks have small-world topology [16] , [20] , [21] , [22] , characterized by their logarithmically scaling average path lengths with network size, despite displaying high clustering.…”
Section: Introductionmentioning
confidence: 99%